Ideologi dan hegemoni kekuasaan dalam novel Hujan Karya Tere Liye - Sabrina, Silvany Haifa; Nurholis, Nurholis (Universitas Lampung, 2024)
This research aims to analyze the ideology and power hegemony contained in the novel